Loss to initiation on antiretroviral therapy (ART) after voluntary counselling and testing (VCT) - Baloyi, Gift Rirhandzu (University of Limpopo (Medunsa Campus), 2011)
Background: Anecdotal evidence from fixed Voluntary Counselling and Testing (VCT) centres within the public sector indicates, that many patients are lost in the transition from VCT to Human Immunodeficiency Virus (HIV) care and treatment. The actual number of patients who are eligible for antiretroviral ttreatment (ART) after a positive HIV test, but who do not visit the antiretroviral (ARV) clinic to initiate ART, is currently not known. The need to identify the extent of this problem was therefore evident. Objectives: To investigate and describe the procedures and records used at the VCT centres under study. To identify the proportions of patients who fail to proceed through the different steps of the process from VCT to initiation on ART within a period of six months. To make recommendations for interventions aimed at improving the tracking of patients from the VCT entry point to ART initiation. Methods: The study was conducted as an operational research project at Odi and Stanza Bopape VCT centres. The design of the study was descriptive. Data were collected retrospectively and prospectively over a period of four months. Operational procedures and documentation systems at both VCT centres were observed. The records of all patients who tested HIV positive from 1 April 2009 to 30 June 2009 at Odi and Stanza Bopape VCT centres were identified from the VCT registers and selected for the study. Patients who were eligible for ART were identified based on their CD4 count. Eligible patient names were crossreferenced against the SOZO system (electronic patient database) to determine whether they had attended their pre-treatment visits at the ART clinic and whether ARV medicines had been dispensed to them for the first time. Where there was no proof that the patient attended the pre-treatment visits or finally accessed ART at an ARV clinic within six months, the patient was regarded as lost to initiation on ART. Results: The results obtained from the observational phase of the study showed differences in the procedures followed at the two VCT centres. At Odi VCT centre, patients referred for VCT by medical doctors only had an ELISA test and had to return on a different date for the ELISA test results, while patients visiting the VCT centre voluntarily first had a Rapid test and if positive they had an ELISA test on the same day. At Stanza Bopape VCT centre, patients referred by doctors and patients visiting the VCT centre voluntarily had a Rapid test and an ELISA test after a positive Rapid test. The patients at Odi had their CD4 test results interpreted by the nurse at the VCT centre while at Stanza Bopape the results were interpreted by the doctor at the ARV clinic. x iv The study included a cohort of 743 patients who tested HIV positive from April 2009 to June 2009 at Odi and Stanza Bopape VCT centres. Of these patients 344 tested at Odi VCT centre and 399 were tested at Stanza Bopape. The majority of patients at the two VCT centres were female (55% at Odi VCT centre and 59% at Stanza Bopape VCT centre), unemployed and single. At both VCT centres, patients were expected to return for collection of CD4 results within two weeks of the HIV test. At Odi VCT centre, 159 (49.4%; n=322) patients did not return to collect their CD4 results. Of those who returned, only 41.1% (67; n=163) returned within one month. At Stanza Bopape VCT centre 52.8% (210; n=399) patients did not collect their CD4 results. Of the patients who collected their CD4 count results, 51.3% (97; n=189) collected within one month. The Fisher’s exact test revealed no statistically significant difference (P=0.410) between the two VCT centres in terms of patients who returned for their CD4 results collection and those who did not return. More than half of the patients with accessible CD4 counts at Odi presented late for VCT. This was shown by 65.4% (n=275) of patients with CD4 count 200 cells/mm3 during HIV diagnosis. At Stanza Bopape VCT centre 46.6% (n=386) also had CD4 count 200 cells/mm3. The difference in terms of late presentation between the patients from the two clinics was statistically significant (P<0.001; Fisher’s exact test). The ART initiation rate at both VCT centres was found to be low. More than half of the patients eligible for treatment (CD4 200 cells/mm3) at both VCT centres did not initiate ART. This was shown by 59.4% (n=180) of patients at Odi VCT centre and 67.8% (n=180) of patients at Stanza Bopape VCT centre who did not initiate ART. There was no significant difference (P=0.317; Fisher’s exact test) between the two VCT centres in terms of the patients who did not initiate ART. Conclusion: A high percentage of patients who presented for VCT and were eligible for treatment were lost to initiation on ART. The majority of these patients did not return to collect their CD4 results and thus were lost immediately after VCT. These results suggest a need for an urgent intervention that will improve ART uptake. Recommendations: Patients referred by doctors for VCT at Odi VCT centre should have a Rapid test, and if positive they should have an ELISA and CD4 test on the same day to prevent the loss of patients before they even identify their HIV status. The option of a ‘one stop’ VCT and immediate CD4 results, should be further explored due to the unacceptable patient default rates at both VCT centres. A CD4 count machine which x v will provide results immediately on the same day of the test should be utilised. There must be sufficient personnel and equipment to follow-up on patients who do not return for their CD4 results, pre-treatment counselling and ART. The SOZO system should be integrated between the VCT centres and the ARV clinics to improve the flow of patient information between the VCT centre and the ARV clinic. A qualitative study should be conducted to explore reasons for patients not returning to collect their CD4 results. Key words: VCT; loss to initiation; non-uptake; lost in transition; HIV and AIDS
Thesis ((MSc(Med)(Pharmacy))--University of Limpopo (Medunsa Campus), 2011.
Keywords: Antiretroviral therapy, highly active